Integrative Taxonomy Reveals Two New Species of Stalked Barnacle (Cirripedia, Thoracica) From Seamounts of the Western Pacific With a Review of Barnacles Distributed in Seamounts Worldwide - Gan, Zhibin; Xu, Peng; Li, Xinzheng; Wang, Chunsheng (Frontiers in Marine Science, 2020)
Dozens of samples of stalked barnacles were collected from deep-sea seamounts of the tropical western Pacific by remotely operated vehicles during two expeditions in 2017 and 2018. Integrative taxonomy indicates that they represent two new species belonging to the families Scalpellidae and Poecilasmatidae, respectively. In terms of morphology, Arcoscalpellum angularum sp. nov. is distinguished from congeneric species by the angular processes on the dorsum of its soft body and the absence of a caudal appendage, whereas Glyptelasma robustum sp. nov. differs from its congeners in its robust peduncle, semicircular concaved carina, and long filamentary appendages. The validity of the two new species is supported by genetic analyses inferred from COI gene sequences and geographic distribution. To date, very few seamounts in the oceans have been investigated for scientific purposes, and little is known about the barnacles that inhabit these seamounts. A literature search reveals about 112 barnacle species recorded in seamounts mainly in the eastern and western regions of the Pacific Ocean. Existing data are insufficient for research on species speciation and diffusion; still more credible data on the distribution of barnacles in seamounts should be collected.